Research on sociocultural influences on motivation and learning. Volume 2 - Van Etten, Shawn (Emerald Publishing Limited, 2004)
This volume covers topics including: translation issues in cross-cultural research; African American teachers for African American students; the social mediation of metacognition; and cross-cultural similarities and differences in affective meaning of achievement.
Includes index.
Keywords: Motivation in education -- Social aspects -- Cross-cultural studies.; Multicultural education -- Cross-cultural studies.; Metacognition -- Social aspects.; Cross-cultural studies -- Translating.; African American teachers.; African American students.; Education -- Educational Psychology.; Educational psychology.; elektronické knihy; electronic books